PHYTASE PRODUCTION BY Enterobacter cloacae - Suliasih Suliasih; Sri Widawati (BIOTROPIA, 2020)
This study aims to isolate phytase-producing bacteria (PPB), a type of plant growth-promoting rhizobacteria (PGPR), from the Vigna sinensis rhizosphere and to optimize their physicochemical conditions. Phytase is an enzyme that hydrolyzes the phosphoester bonds in organic phosphorus (phytic acid) to release ester phosphate and inorganic phosphate, the bioavailable forms of phosphorus. To test their ability to hydrolyze organic phosphates (calcium phytate), phytase activity was screened using solid and liquid phytase screening medium (PSM). A total of 13 isolates tested positive for phytase production, indicated by clear hydrolysis zones surrounding the colonies. Enterobacter cloacae strain B1 exhibited the highest hydrolysis efficiency (3.43) on solid medium. The phytase produced by E. cloacae strain B1 in liquid PSM reached 0.92 U/mL after 48 hours of incubation. This strain produced optimal phytase levels in the presence of lactose and monoammonium phosphate (NH₄H₂PO₄) as carbon and nitrogen sources, respectively, at 30 °C and pH 5.0. The PPB obtained in this study are recommended for further research regarding their potential use as biological fertilizers for plants.